The Influence of AIMOHit to Medication Adherence of Hypertension Patients in Malang - Alfrina Hany; Klara Yunita Inuq Thomas; Ahmad Hasyim Wibisono (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2021)
The long-term treatment that a hypertensive patient has to undergo has resulted in the patient becoming non-adherent. Patients accidentally not taking medication is one of the causes of non-adherence. A method for preventing non-compliance due to forgetting to take medication is important. The AIMOHit application which means